Evidence- Based Interventions for Functional Restoration and Pain Management following Traumatic Brain Injury - Kandikattu, Sugeeth; Aavula, Manas; Parvizi, David; Agrawal, Devendra K (Archives of Clinical and Medical Case Reports, 2026)
Traumatic brain injury is a major cause of death and long-term disability worldwide and can lead to persistent functional impairment and chronic pain that significantly impact quality of life. Patients with traumatic brain injury commonly experience motor deficits, impaired balance and coordination, cognitive dysfunction, and behavioral changes. Chronic pain, particularly post-traumatic headaches and musculoskeletal pain, is also frequently reported and can limit participation in rehabilitation and daily activities. This narrative literature review summarizes current evidence on the epidemiology, pathophysiology, and clinical course of traumatic brain injury, with a focus on functional restoration and pain management. Existing research supports the use of multidisciplinary rehabilitation approaches that incorporate physical therapy, occupational therapy, cognitive rehabilitation, and structured exercise to improve recovery and independence. In addition, both pharmacologic and non-pharmacologic pain management strategies play an important role in addressing chronic symptoms and supporting rehabilitation efforts. Overall, early recognition of functional deficits and integrated rehabilitation strategies are essential for improving long-term outcomes and quality of life in patients with traumatic brain injury.